Psychological Science and Linguistic Theory - Francis, Norbert (Verbum, 2026)
In the study of human cognition, language is central in part because our species is the only surviving member of the primate lineage that is in possession of its distinctive properties. Evidence suggests that only in homo sapiens, spectacularly, did language emerge. Aside from the point of view of evolutionary origins, the other reason for language being a defining feature is its function as an indispensable instrument of higher order cognition. If language-related abilities are essential in this way, linguistics can be understood as a branch of psychology; and in general, the methods of cognitive science should be applicable to its study in every way. From another perspective, its centrality is related to the interconnectivity of language with the other higher order competencies of the mind. Thus, in all of the above, and in the following discussion, “language” should be understood as “knowledge of language.” As in all the branches of psychology, rooted in turn in biological science, attention to the relationship between applied research and theory cannot in the long run be neglected.